Real-world results of first-line immunotherapy or targeted therapy for metastatic melanoma in Finland: a cohort study - Mattila, Kalle E; Tiainen, Leena; Vikkula, Johanna; Kreutzman, Anna; Engström-Risku, Mia; Kysenius, Kai; Hölsä, Olivia; Hernesniemi, Sari; Hemmilä, Päivikki; Pystynen, Anssi; Mäkelä, Siru (Informa UK Limited, 2025)
Aim: First-line (1L) immunotherapy has yielded superior overall survival (OS) in metastatic melanoma (MM) but some patients are ineligible for immunotherapy or need rapid response with 1L targeted therapy (TT).
Materials & methods: Retrospective cohort study of real-world patients treated with 1L immunotherapy (144 BRAF wild type, 85 BRAF-mutated) or 1L TT (143 BRAF-mutated) for MM in Finland during 2014-2021.
Results: Baseline brain metastases, liver metastases and elevated LDH were less common, 2-year OS rates were higher (60.3-63.5% vs. 33.8%) and more patients were alive without the next-line treatment (38.0-43.8% vs. 23.3%) in patients with 1L immunotherapy.
Conclusion: Real-world patients with 1L immunotherapy for MM had favorable baseline characteristics and better treatment outcomes than observed in patients with 1L TT.